(untitled) (The International Research Journal of Management Science, 2022)
Purpose- This paper attempts to evaluate the synergistic effect of the merger on financial performance, market share, and the wealth of the shareholders of the selected BFIs. Methodology- Two cases of mergers of commercial banks have been taken as samples for the study. First is the merger between Prabhu Bank Limited and Grand Bank Limited (forming Prabhu Bank Limited) and second is the merger between Lumbini Bank Limited and Bank of Kathmandu Limited (forming Bank of Kathmandu Limited). Both the mergers happened in 2016. To analyze the mentioned variables of the selected BFIs, pre-merger (2011–2015) and post-merger (2016–2020) data have been compared using a t-test and regression analysis. Findings- The result of the study reveals that there is a significant relationship between financial performance and shareholder value and the merger, whereas there is no relationship between the market share of the BFIs and the merger. Practical implication- The study concludes that to achieve improved post-merger financial efficiency and reap the benefits of an improved financial position, merged BFIs should be more aggressive in their profit drive and maintain better asset qualities. Originality/ Value- This study can become a foundation for future studies in the Nepalese context of the merger of BFIs.